Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

let $G$ be a free abelian group of rank $n$ with basis $B=\{b_1,\cdots,b_n\}$ then $G$ must be torsion-free. to prove this let $g=\sum{m_ib_i}\not = 0$ an element of $G$. Suppose there exists $q\in \mathbb Z$ such that $qg=0$ then $\sum{qm_ib_i}=0$, so for each $i=1..n$, $qm_i=0$. Now since $g\not = 0$ then $q=0$. Is this correct?

share|cite|improve this question
What's your definition of free abelian group? – Jason DeVito Mar 7 '12 at 15:13
a "free abelian group" $G$ on a basis $B=\{b_1,\cdots,b_n\}$ (this is the finite case): for each $g\in G$ there is a unique sequence of integers $m_1,\cdots,m_n$ such that $g=m_1b_1+\cdots+m_nb_n$ – palio Mar 7 '12 at 15:19
Then uniqueness is key. If there is an element which is torsion, say $q g=0$, then $0$ has 2 expressions: $qg$ and $0$. – Jason DeVito Mar 7 '12 at 15:21
you mean $qg$ and $0g$ both are $0$ so there is two integers $q$ and $0$ but here $g$ need not be a basis element. so we can't conclude i think unless we do all the work above – palio Mar 7 '12 at 15:26
But $g$ is made out of basis elements. Say $g = \sum m_i b_i$. Then since $g\neq 0$, at least one $m_j\neq 0$. Then $0 =qg = \sum (qm_i)b_i$ and $qm_j\neq 0$. So, you've written $0$ in a way where not all coefficients are $0$. Since using all coefficients $0$ is another way, you've violated uniqueness. – Jason DeVito Mar 7 '12 at 15:28

Your proof is correct. However, I would add one more step to "since $g \neq 0$ then $q = 0$":

Since $g \neq 0$ and $b_1,\ldots,b_n$ are linearly independent $m_i \neq 0$ for some $i$. Because $\mathbb Z$ has no zero divisors $qm_i = 0$ implies $q = 0$.

EDIT: It is not necessary to restrict to the finite rank case. Your basis may have any cardinality, however, since $g$ can be expressed as a finite linear combination of basis elements the proof works the same in that case.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.